HIV As Trojan Exosome: Immunological Paradox Explained? - Hildreth, James E. K. (Frontiers in Immunology, 2017)
The HIV pandemic is still a major global challenge despite the widespread availability of antiretroviral drugs. An effective vaccine would be the ideal approach to bringing the pandemic to an end. However, developing an effective HIV vaccine has proven to be an elusive goal. Three major human HIV vaccine trials revealed a strong trend toward greater risk of infection among vaccine recipients versus controls. A similar observation was made in a macaque SIV vaccine study. The mechanism explaining this phenomenon is not known. Here a model is presented that may explain the troubling results of vaccine studies and an immunological paradox of HIV pathogenesis: preferential infection of HIV-specific T cells. The central hypothesis of this perspective is that as “Trojan exosomes” HIV particles can directly activate HIV-specific T cells enhancing their susceptibility to infection. Understanding the biology of HIV as an exosome may provide insights that enable novel approaches to vaccine development.